1992
DOI: 10.1002/j.1460-2075.1992.tb05139.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the nuclear receptor gene superfamily.

Abstract: Nuclear receptor genes represent a large family of genes encoding receptors for various hydrophobic ligands such as steroids, vitamin D, retinoic acid and thyroid hormones. This family also contains genes encoding putative receptors for unknown ligands. Nuclear receptor gene products are composed of several domains important for transcriptional activation, DNA binding (C domain), hormone binding and dimerization (E domain). It is not known whether these genes have evolved through gene duplication from a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
332
0
15

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 644 publications
(363 citation statements)
references
References 79 publications
16
332
0
15
Order By: Relevance
“…The AR, together with the receptors of glucocorticoid, progesterone and mineralocorticoid, are closely related members (class I) in the nuclear receptor superfamily. 22 They all recognize similar response elements (steroid response element, SRE), which are organized as inverted repeats of 5 0 -TGTTCT-3 0 -like sequences with a threenucleotide spacer. 23 We and others have shown that SGK-1 expression is regulated by glucocorticoid via an imperfect glucocorticoid response element (GRE) on the sgk1 promoter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AR, together with the receptors of glucocorticoid, progesterone and mineralocorticoid, are closely related members (class I) in the nuclear receptor superfamily. 22 They all recognize similar response elements (steroid response element, SRE), which are organized as inverted repeats of 5 0 -TGTTCT-3 0 -like sequences with a threenucleotide spacer. 23 We and others have shown that SGK-1 expression is regulated by glucocorticoid via an imperfect glucocorticoid response element (GRE) on the sgk1 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Reporter gene assay showed that the promoter fragment containing this GRE motif was activated by androgen treatment at AR-dependent manner in LNCaP cells that are null of glucocorticoid receptor (GR). 35 Because the AR and the GR are closely related members in the steroid hormone receptor family, 22 it is plausible that this GRE (termed as ARE-1) motif is involved in androgen-induced SGK-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NOR-2 contains two zinc-fingers of the C2C2 type, as do of the members of this family [16]. While we finished the sequencing of NOR-2, a second computer analysis showed that this factor was identical, from ATG (at 487 nt) until 1,746 nt, to NOR-1 which has been very recently identified [10].…”
Section: Structural Characteristics Of Nor-2 Cdna and Homology To Thementioning
confidence: 89%
“…Our analysis revealed that the pattern of gene duplication events that explain the present diversity of Rel/NF-kB and IkB families is very similar to what happened for other transcription factor families. We previously demonstrated that the diversity of ETS genes and nuclear receptors, as for the Hox/HOM or Myc families, arises very early during metazoan evolution and then increases speci®cally in the vertebrate lineage (Atchley and Fitch, 1995;Holland and Garcia-Fernandez, 1996;Laudet et al, 1992Laudet et al, , 1993. Likewise, the existence of paralogous members such as c-Rel, RelA and RelB or NF-kB1 and NF-kB2, shows that the diversity of Rel/NF-kB or IkB families members was also increased during the vertebrate evolution.…”
Section: Discussionmentioning
confidence: 99%